Rapid quantification of mcyB copy numbers on dry chemistry PCR chips and predictability of microcystin concentrations in freshwater environments - Henna Savela; Markus Vehniäinen; Lisa Spoof; Sonja Nybom; Jussi Meriluoto; Urpo Lamminmäki (My University, 2022)
Microcystin-producing cyanobacteria cause serious water quality problems worldwide, which has led to growing pressure for more intensive monitoring. Molecular biology methods that are based on identification and enumeration of biosynthetic genes, such as quantitative PCR, show promise in this respect. To be practical in a wide range of settings, these methods need to be usable also by laboratory personnel who do not have previous experience in PCR setup. Here we present a real-time quantitative mcyB dry chemistry PCR assay capable of identifying the three globally most common microcystin-producing cyanobacterial genera, Anabaena, Microcystis and Planktothrix. It minimizes the amount of liquid handling and avoids direct contact with the PCR reagents at the time of analysis. Large quantities of virtually identical chips can be manufactured, improving the comparability of results. Using the dry chemistry PCR chips, freshwater environmental samples from Finnish and Estonian lakes, rivers and reservoirs were analyzed for mcyB. The chip format was found to be highly suitable for water sample analysis due to its ease-of-use, good sensitivity and amplification efficiency. Significant positive correlation (Spearman's rank correlation, ρ > 0.66, P < 0.001) was observed between combined mcyB copy numbers from Microcystis, Anabaena, Planktothrix and total microcystin concentrations, regardless of the method used to measure the toxins (ELISA or LC–MS). Positive correlations were observed also for single lakes.